2001
DOI: 10.1002/jmv.2001.abs
|View full text |Cite
|
Sign up to set email alerts
|

Changing prevalence of hepatitis C virus genotypes: Molecular epidemiology and clinical implications in the hepatitis C virus hyperendemic areas and a tertiary referral center in Taiwan

Abstract: To determine the hepatitis C virus (HCV) genotype distribution in Taiwan and to clarify the relationship between genotype and the pathogenesis of HCV infection, 1,164 subjects positive for serum HCV antibodies and HCV RNA from three HCV hyperendemic areas (Masago, Tzukuan, and Taoyuan) and a tertiary referral center in Taiwan were studied during 1995-1997. HCV genotypes and viral loads were determined using Okamoto's method and branched DNA assay, respectively. Genotype 1b was the most prevalent in Tzukuan (61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 0 publications
7
48
2
Order By: Relevance
“…The similar epidemiological situation was also described in other former Soviet Union Republics, and most Asian countries, such as Moldova, Russia, Belarus, Mongolia [Lvov et al, 1996;Viazov et al, 1997]; Taiwan [Yu et al, 2001]; China ; and Japan [Noguchi et al, 1997], where genotype 1b is also common. Genotype 3a found in 25.0% of all cases typed was second most common type in the country.…”
Section: Discussionsupporting
confidence: 61%
“…The similar epidemiological situation was also described in other former Soviet Union Republics, and most Asian countries, such as Moldova, Russia, Belarus, Mongolia [Lvov et al, 1996;Viazov et al, 1997]; Taiwan [Yu et al, 2001]; China ; and Japan [Noguchi et al, 1997], where genotype 1b is also common. Genotype 3a found in 25.0% of all cases typed was second most common type in the country.…”
Section: Discussionsupporting
confidence: 61%
“…In previous studies utilizing reverse transcription polymerase chain reaction (RT-PCR) with type-specifi c primers [26][27][28] , 58-73% of HCV isolates from northern Taiwan were found to be genotype 1b and 7.4-16.5% genotype 2a [27][28][29] , while around 48-64.3% were genotype 1b and 35-41% genotype 2a in southern Taiwan [27,30] .…”
Section: Prevalence Of Hcv Genotypes and Their Infl Uence On The Progmentioning
confidence: 99%
“…Our study suggested that independent HCV outbreaks continue in hyperendemic areas in Taiwan, and that the HCV infection keeps changing along with the relative prevalence of HCV genotypes in relation to age. Both the correlation of genotype 1b with age (cohort effect) and intrinsic properties of HCV genotypes are probably responsible for the association between genotype and pathogenesis of HCV infection [29] .…”
Section: Distribution Of Hcv Genotypes In Southern Taiwanmentioning
confidence: 99%
“…In addition, several areas hyperendemic for HCV have been discovered in southern Taiwan [16][17][18][19] ; the molecular epidemiology of HCV may differ in these areas. In 1,164 subjects positive for anti-HCV and HCV RNA in serum from three HCV hyperendemic areas (community-based; Masago, Tzukuan and Taoyuan) and a tertiary referral center (hospitalbased) in southern Taiwan, we determined genotype distribution to evaluate the age-specifi c prevalence of HCV genotypes and clarify the relationship between genotype and pathogenesis of HCV infection [29] ; HCV genotypes were examined by the method of Okamoto et al [30] . HCV genotypes were able to be determined in 1,100 of 1,164 (94.5%) subjects.…”
Section: Distribution Of Hcv Genotypes In Southern Taiwanmentioning
confidence: 99%